Isolating hydrogen in hexagonal boron nitride bubbles by a plasma treatment - Li He (Nature Portfolio, 2019)
Hexagonal boron nitride (hBN) is a two-dimensional material with wide band gap and high thermal and chemical stability. Here the authors demonstrate the formation and trapping of hydrogen gas bubbles in hBN interlayers upon plasma treatment, promising for extracting and storing hydrogen.